The effectiveness of social skill training on depressive symptoms, self- esteem and interpersonal difficulties among Schizophrenic patients - I. El Malky, Maaly; Atia, Mervat; H.Alam, Faten (International Journal of Advanced Nursing Studies, 2016)
Patients with social skills deficits such as problems with communication with other people, social withdrawal, problems with activities of daily living should be offered to social skills training. Patients with schizophrenia usually have social skills deficits. Social skills training is a set of systematic techniques and strategies useful for teaching interpersonal skills that are based on social learning theory. It is a widely used treatment of a range of psychiatric disorders as schizophrenia. The aim of this study was to examine the effectiveness of social skill training program on self-esteem, depression and interpersonal difficulties among schizophrenic patients. Design: Quasi-experimental design (one group pretest posttest design) was used to achieve the aim of the study. Setting: The study was conducted at The Psychiatric Hospital in Tanta and the Psychiatric Hospital in Mit-Khalf at Menoufyia, Egypt. Sample: A convince sample (50) was selected in the chosen setting inpatient department. Tools: four tools were used for data collection. Tool one: a structured: socio-demographic questionnaire to obtain demographic data about the studied sample. Tool two: The depression, anxiety and stress scale (DASS).In this paper the researcher used the depression scale only which consists of 14 items in the form of rating scale. The depression scale assesses dysphoria, hopelessness, and devaluation of life, self- deprecation, and lack of interest and anhedonia. Tool three: Self- Esteem Inventory Scale: It evaluates attitudes of individuals toward themselves and consists of 25 items. Tool four: Relationship Scales Questionnaire. It consists of 13 items five points Likert- scale. The results: There is a highly significant reduction of the mean score of depressive symptoms and interpersonal difficulties at 0.001 while highly significant increase of the mean score of self-esteem at 0.001 post program than pre program. Conclusion: The social skills training program had a positive effect on interpersonal difficulties, depressive symptoms and self-esteem of the schizophrenic patients after receiving social skill training program. Recommendations: Generalized of social skill training program for all psychotic patients in hospital to improve their social competence and self-esteem.